(untitled) (International Journal of Food and Nutritional Sciences, 2023)
This research examines the role of ethical practices on the performance of small and medium-sized enterprise (SME) in Jalgaon district of Maharashtra state in India. As more businesses take a more sustainable and responsible approach in conducting operations, the study compares the impact of ethical aspects (wage equity, adherence to laws governing labor practices, transparency, environmental consciousness, and corporate social responsibility (CSR) activities) on key performance indicators, namely, staff retention, customer satisfaction, operational efficiency, and profitability. A 150 sample of SMEs that used secondary data were used to come up with an Ethical Practice Index (EPI) and a Composite Performance Score. The average EPI score was at 3.00 (scale 1-5) and performance at 61.58. The correlation analysis showed that there is a positive relationship with a weak strength (r = 0.05) between ethical practices and performance. Nonetheless, average performance levels were incredibly higher in firms in High-EPI group (64.02) than the in firms in Low (61.44) and Very Low groups (61.68). Given the findings, although ethics is not the only motivating factor in performance, failure to attain ethical standards is typically associated with inefficiencies in the operation and negative results. The analysis indicates that ethical integrity is a contributing factor of long-term competitiveness and policy formulation to enable ethical compliance among regional SMEs should be conducted through structured policy interventions.